The Influence of Youtube Ads on Purchase Intention - Willy Kristian; RA Dyah Wahyu Sukmaningsih; Eric Gunawan; Rafy Pranadya Annaufal; Rafi Giffari (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2023)
The high number of social media users on YouTube has made many companies interested in advertising on the platform. However, many YouTube users tend to skip the ads that are displayed. The main objective of this research is to determine the factors within YouTube ads that have an influence on Purchase Intention. This study uses a quantitative research method, with variables including Informativeness, Entertainment, Customization, Irritation, Advertising Value, Flow Experience, Brand Awareness, and Purchase Intention. The results of this research show that Informativeness has a significant influence on Advertising Value but not on Flow Experience. Meanwhile, Entertainment and Customization have a significant influence on both Advertising Value and Flow Experience, and Advertising Value, Brand Awareness, and Flow Experience have a significant influence on Purchase Intention. As for Irritation, this variable does not have a significant influence on Advertising Value and Flow Experience.